Hubungan Perilaku Personal Hygiene terhadap Kejadian Kecacingan dan Stunting Pada Siswa Kelas I-III di SDN Pematang Limau, Kabupaten Gunung Mas - Astri Widiarti; Ni Nyoman Sri Yuliani; Indria Augustina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
One of the factors causing stunting is an infectious disease caused by helminthiasis. Worm infection is the entry of parasites in the form of worms into the human body. This infection can cause a decrease in nutritional status, endurance, intelligence and productivity of sufferers. Riskesdas 2018 data shows that the prevalence of stunting in Gunung Mas exceeds the national stunting rate. Primary school-age children, especially grades I, II and III, are vulnerable to helminthiasis because children of this age are still very actively playing on the ground and pay little attention to personal hygiene. Based on a survey conducted in 10 districts in 2012, it was found that the highest prevalence of helminthiasis came from the Gunung Mas district of Central Kalimantan province (76.67%). Pematang Limau State Elementary School in Pematang Limau Village, Sepang District, Gunung Mas Regency is in a watershed area which is a high-risk area for worm infection transmission. The purpose of this research to find out the relationship between personal hygiene behavior toward worm and stunting incidents in class I-III students at SDN Pematang Limau, Gunung Mas Regency. The method is using the analytic observation method with a cross-sectional approach. In this study, the independent variables are personal hygiene behavior and the dependent variable is the occurrence of intestinal worms and stunting. The results are shown that the incidence of helminthiasis in class I-III students were influenced by factors of poor personal hygiene behavior. The stunting incident found in this study was not related to the respondent's personal hygiene behavior.